Linking TRIZ to Conceptual Design Engineering Approaches. (2015) - Frillici, Francesco Saverio; Fiorineschi, Lorenzo; Cascini, Gaetano
Abstract: During the last decades, product design has yielded several interest by scholars, leading to a great amount of contributions concerning design methodology. Some of them, beyond modeling the whole design process, propose their model of the early design activities devoted to the development of the product concept, i.e. the conceptual design phase. These design approaches are widely diffused in academia. However, some uncertainties appear in literature, concerning their efficacy in performing innovative design. This observation forms the basis of this work, which aims at improving classical design processes by integrating their procedure with the TRIZ base of knowledge. To achieve such an objective, authors' approach consists in considering generally valid steps of the conceptual design process, and then in identifying most suitable TRIZ tools for each of them. A structured list of suggestions concerning the proposed integration is finally presented, together with an explanatory case study application of the proposed improvements.